Scientific Opinion on the safety and efficacy of Cygro® 10G (maduramicin ammonium‐α) for turkeys. (18th February 2015) - ,; ,
Abstract: Cygro ® 10G is a coccidiostat for turkeys for fattening containing 10 g of the polyether ionophore maduramicin ammonium‐α (Maα)/kg additive. The maximum proposed dose (5 mg Maα/kg) is considered safe for turkeys with a margin of safety of 2.5. It is unlikely that there will be any measurable adverse effects of Maα on the overall gut flora. Maα is absorbed and excreted rapidly. O ‐demethylation is the main metabolic pathway in turkeys and rats. Maduramicin‐α is the marker residue in the liver and skin/fat. Maα is not mutagenic or carcinogenic. The lowest no observed adverse effect level (NOAEL) of 0.1 mg/kg bw per day is found in chronic and multi‐generation studies in rats. An acceptable daily intake (ADI) of 1 mg Maα/kg bw (60 μg per person) is derived, applying an uncertainty factor of 100. After a three‐day withdrawal, human exposure to maduramicin residues complies with the ADI (17 %). Maximum residue limits (MRL) of 0.15 mg maduramicin/kg liver and skin/fat, 0.1 mg/kg kidney and 0.03 mg/kg muscle are proposed. Although Cygro ® 10G is not an irritant to skin or eyes or a dermal sensitiser, any direct dermal contact should be avoided owing to the high systemic toxicity of Maα after dermal application. Inhalation of Cygro ® 10G is considered a hazard; therefore a risk to persons handling the additive cannot be excluded. The use of Cygro ® 10G is safe for the environment, with the exception of soils with pH values above 7.2, for which no data were available. This conclusion does not extend to effects on organisms living on manure which are not assessed under the current regulation. Based on the recent studies (floor pen studies, field studies and sensitivity studies), the efficacy of Cygro ® 10G in turkeys for fattening has not been sufficiently demonstrated.